Spiegare il ragionamento e i passaggi.
Ricordiamo che l'integrale seguente si risolve per parti
$ \int arctan(x) dx = $
per cui
$ = x \cdot arctan(x) - \int \frac{x}{x^2+1} \, dx =$
rendiamolo immediato
$ = x \cdot arctan(x) - \frac{1}{2} \int \frac{2x}{x^2+1} \, dx =$
$ = x \cdot arctan(x) - \frac{1}{2} ln(x^2+1) + c $
Fatta questa premessa
$ F(x) = \int_1^x arctan(t) \, dt $
$= \left. t \cdot arctan(t) - \frac{1}{2} ln(t^2+1) \right|_1^x $
$= x \cdot arctan(x) - \frac{1}{2} ln(x^2+1) - \frac{\pi}{4} + \frac{1}{2} ln(2) $
$= x \cdot arctan(x) - \frac{1}{2} ln(\frac{x^2+1}{2}) - \frac{\pi}{4} $